A Bilevel approach to optimize electricity prices - Alekseeva, Ekaterina; Brotcorne, Luce; Lepaul, Sebastien; Montmeat, Alain (Yugoslav Journal of Operations Research; Vol 29 No 1 (2019), 2018)
To meet unbalanced demand an energy provider involves costly generation technologies which in turn result in high residential electricity prices. Our work is devoted to the application of a bilevel optimization, which is a challenging class of optimization problems in the electricity market. We propose an original demand-side management model, adapt a solution approach based on complementary slackness conditions and provide the computational results on illustrative and real data. The goal is to optimize hourly electricity prices taking into account the consumers' behavior and minimizing energy generation costs. Choosing new pricing policy and shifting some consumption from peak to off-peaks hours the consumers might decrease their electricity payments and eventually decrease the energy generation costs.